Unusual swelling behavior of polymer-clay nanocomposite hydrogels - ABDURRAHMANOĞLU, SUZAN (ELSEVIER SCI LTD, 2007)
The swelling behavior and the elastic properties of nanocomposite hydrogels have been investigated. The hydrogels were prepared by freeradical polymerization of the monomers acrylamide (AAm), N,N-dimethylacrylamide (DMA), and N-isopropylacrylamide (NIPA) in aqueous clay suspensions at 21 degrees C. Laponite with a radius of gyration in distilled water of 20 nm was used as clay particles in the hydrogel preparation. The reactions with AAm monomer were carried out in the presence of the chemical crosslinker N,N-methylenebis(acrylamide) (BAAm). It was found that the volume of nanocomposite hydrogels immersed in water rapidly increases and attains a maximum value after about one day. Surprisingly, further increase in the swelling time results in the deswelling of the gels until they reach a limiting swelling ratio after about 5 days. This unusual swelling behavior is observable only when the clay concentration in the hydrogel is above the overlap threshold c*. Swelling measurements combined with the elasticity tests show that the effective crosslink density first decreases, but then increases with increasing time of swelling of the hydrogels. The results were explained in terms of the rearrangements of the highly entangled polymer chains and clay particles during the gel volume change. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: nanocomposite hydrogels; clay; swelling; SPATIAL INHOMOGENEITY; ELASTICITY; POLY(N,N-DIMETHYLACRYLAMIDE); POLY(N-ISOPROPYLACRYLAMIDE); SCATTERING; GELS